A Sucrose‐Mediated Sol–Gel Technique for the Synthesis of MgO–Y2O3 Nanocomposites. Issue 2 (28th December 2012) - Iyer, Aparna; Garofano, Jacquelynn K.M.; Reutenaur, Justin; Suib, Steven L.; Aindow, Mark; Gell, Maurice; Jordan, Eric H.
Abstract : A sucrose‐mediated aqueous sol–gel procedure was developed to synthesize MgO–Y2 O3 nanocomposite ceramics for potential optical applications. The synthesis involves the generation of a precursor foam containing Mg 2+ and Y 3+ cations via the chemical and thermal degradation of sucrose molecules in aqueous solution. Subsequent calcination and crushing of the foam gave MgO–Y2 O3 nanocomposites in the form of thin mesoporous flake‐like powder particles with uniform composition and surface areas of 27–85 m 2  g − 1, depending on calcination conditions. The flakes exhibited a homogeneous microstructure comprising intimately mixed nanoscale grains of the cubic MgO and Y2 O3 phases. This microstructure was resistant to grain coarsening with average grain sizes of less than 100 nm for calcination temperatures of up to 1200°C. The results indicate that the sucrose‐mediated sol–gel process is a simple effective method for making nanoscale mixed oxides.